Effects of ABO incompatibility on the outcome of allogeneic hematopoietic stem cell transplantation. (April 2020) - Parkhideh, Sayeh; Chegeni, Rouzbeh; Mehdizadeh, Mahshid; Roshandel, Elham; Tavakoli, Farzaneh; Hajifathali, Abbas
Abstract: Background: ABO compatibility between donor and recipient is no necessary in allogeneic hematopoietic stem cell transplantation (AHSCT). Incompatible transplantations can be divided into three groups based on the donor and recipient blood groups. The influence of each kind of incompatibilities on the outcome of patients does not seem to be consistent. This study aimed to investigate the outcome of AHSCT patients focusing on compatibility statues. Method: This retrospective study was conducted on 186 patients who underwent first AHSCT, includes 108 identical, 38 minor, 32 major and eight bidirectional ABO incompatible recipients. Comparative analysis was performed for common clinical transplantation outcomes. Results: There was no statistically significant association between ABO incompatibility and graft-versus-host disease, WBC or platelet engraftment, and transfusion requirement. WBC engraftment rate was significantly lower in minor-incompatible patients. Furthermore, total and direct bilirubin which (the hemolysis biomarkers) were considerably higher in the bidirectional incompatible group, compared to the other patients. Conclusion: Our results indicate that the ABO incompatibility might be an effective factor in engraftment time and laboratory hemolysis. Elucidating the impact of ABO incompatibility on the clinical outcome of patients warrants an extended and deep investigation in a large-scale study with comprehensive variables such as survival, relapse, and other complication of transplantation.